CTLA4 Message Reflects Pathway Disruption in Monogenic Disorders and Under Therapeutic Blockade - Garcia-Perez, Josselyn E.; Baxter, Ryan M.; Kong, Daniel S.; Tobin, Richard; McCarter, Martin; Routes, John M.; Verbsky, James; Jordan, Michael B.; Dutmer, Cullen M.; Hsieh, Elena W. Y. (Frontiers in Immunology, 2019)
CTLA-4 is essential for immune tolerance. Heterozygous CTLA4 mutations cause immune dysregulation evident in defective regulatory T cells with low levels of CTLA-4 expression. Biallelic mutations in LRBA also result in immune dysregulation with low levels of CTLA-4 and clinical presentation indistinguishable from CTLA-4 haploinsufficiency. CTLA-4 has become an immunotherapy target whereby its blockade with a monoclonal antibody has resulted in improved survival in advanced melanoma patients, amongst other malignancies. However, this therapeutic manipulation can result in autoimmune/inflammatory complications reminiscent of those seen in genetic defects affecting the CTLA-4 pathway. Despite efforts made to understand and establish disease genotype/phenotype correlations in CTLA-4-haploinsufficiency and LRBA-deficiency, such relationships remain elusive. There is currently no specific immunological marker to assess the degree of CTLA-4 pathway disruption or its relationship with clinical manifestations. Here we compare three different patient groups with disturbances in the CTLA-4 pathway – CTLA-4-haploinsufficiency, LRBA-deficiency, and ipilimumab-treated melanoma patients. Assessment of CTLA4 mRNA expression in these patient groups demonstrated an inverse correlation between the CTLA4 message and degree of CTLA-4 pathway disruption. CTLA4 mRNA levels from melanoma patients under therapeutic CTLA-4 blockade (ipilimumab) were increased compared to patients with either CTLA4 or LRBA mutations that were clinically stable with abatacept treatment. In summary, we show that increased CTLA4 mRNA levels correlate with the degree of CTLA-4 pathway disruption, suggesting that CTLA4 mRNA levels may be a quantifiable surrogate for altered CTLA-4 expression.